2000
DOI: 10.3168/jds.s0022-0302(00)75161-7
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Estimating Daily Yield from Single Milk Testing Schemes and Use of a.m.-p.m. Records in Test-Day Model Genetic Evaluation in Dairy Cattle

Abstract: Statistical models were presented to estimate daily yields from either morning or evening test results. The 64,451 test-day records from 10,392 lactations of 8800 cows were available for analysis from experiments that were designed to investigate the accuracy of an alternate morning and evening four-weekly milk-testing scheme. The experiments were conducted in 152 herds from six German states and covered a span from 1994 to 1998. Milk yield, fat, and protein percentage were recorded for all of the morning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
57
1
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 14 publications
16
57
1
7
Order By: Relevance
“…Determined correlations, regardless of estimation method or breed, were high and statistically highly significant (P<0.0001), indicating the adequacy of using method M 1 in routine work. Similar correlations were obtained by Liu et al (2000), while Wiggans' study (1986) showed higher projection error in Holstein cattle than in the Jersey breed.…”
Section: Descriptive Statisticssupporting
confidence: 73%
See 4 more Smart Citations
“…Determined correlations, regardless of estimation method or breed, were high and statistically highly significant (P<0.0001), indicating the adequacy of using method M 1 in routine work. Similar correlations were obtained by Liu et al (2000), while Wiggans' study (1986) showed higher projection error in Holstein cattle than in the Jersey breed.…”
Section: Descriptive Statisticssupporting
confidence: 73%
“…Estimation based on evening milk yield resulted in slightly lower correlations. Similar relationships between estimated and true daily milk yield were determined by Liu et al (2000); in their study correlations ranged from 97.6% to 97.7% when estimated from morning milkings, and from 95.8% to 97.4% when estimated from evening milkings. The highest mean differences between estimated and true daily milk yield i.e.…”
Section: Descriptive Statisticsmentioning
confidence: 55%
See 3 more Smart Citations